Road Speed Breakers Power Generation - Ammar A., Al Talib; Abdel Wahab, Sameer; Amar, Rizuan; Sarah, Atifah; Ayu, Idayu (INTI International University, 2023)
The relentless and unchecked rise in global energy consumption necessitates the development of innovative energy generation methods. Renewable energy offers a promising solution, utilizing lost energy and addressing both environmental and engineering concerns. As the number of registered cars on roads increases, traffic, pollution, and energy usage surge, highlighting the need for sustainable alternatives. This study aims to create and evaluate a power-generating speed bump, effectively capturing the energy dissipated during vehicle braking on speed breakers. Employing an innovative mechanism of rack and pinion, complemented by a compound gear train. The proposed solution combines the strengths of existing designs while rectifying their drawbacks through component integration. To ensure long-term reliability, the mechanism undergoes ANSYS simulations. The direction of passing over the bump and the weight of the passing load have been studied in this research. Each trial was repeated for 20 times, and the average value was considered to ensure the reliability of results. A maximum and minimum power generation of 35.6W and 23.4W have been obtained.